The New Synagogue in Poznań. A Forgotten Legacy of the Jewish Community of Poznań? (Geography and Tourism, 2024)
Poland is a country which features numerous sites associated with Jewish culture, including former synagogues. Many were rebuilt after World War II when they lost their religious function. Some of them remain undeveloped. A neglected site with an interesting history is the New Synagogue in Poznań, a living testimony to the history of the Jewish community of Poznań. This paper aims to present the New Synagogue, an example of a forgotten, non-utilised element of Jewish cultural heritage, that simultaneously has a potential tourist value. The research methods included desk research, field observation and a survey seeking the opinions of the New Synagogue from the inhabitants of Poznań. The outcomes imply that the synagogue's future is an important topic for the city residents. The respondents believe that the building if adapted for cultural purposes might add considerable value to the tourism offer of Poznań and reveal its multiculturalism, which is rarely highlighted these days.PL:Polska jest krajem, gdzie znajduje się wiele pamiątek kultury żydowskiej, w tym dawnych synagog. Wiele z tych obiektów po II wojnie światowej, kiedy to utraciły swoją sakralną funkcję, zostało odbudowanych. Część dalej pozostaje niezagospodarowana. Obiektem zaniedbanym, o ciekawej historii jest Nowa Synagoga w Poznaniu, będąca świadectwem historii poznańskich Żydów. Celem niniejszego artykułu jest ukazanie Nowej Synagogi, będącej przykładem zapomnianego, niewykorzystanego elementu dziedzictwa kultury żydowskiej, mającego jednocześnie potencjalny walor turystyczny. Metodyka przeprowadzonych badań obejmowała desk research, obserwację terenową oraz badanie ankietowe dotyczące opinii poznaniaków na temat Nowej Synagogi. Na podstawie wyników badań można wnioskować, że przyszłe losy obiektu są ważnym tematem dla mieszkańców miasta. Zdaniem respondentów, budynek zaadaptowany do celów kulturowych mógłby znacząco wzbogacić ofertę turystyczną Poznania i ukazać jego wielokulturowe, rzadko podkreślane dziś oblicze.